Indole: A promising scaffold for the discovery and development of potential anti-tubercular agents - Nilesh Gajanan Bajad; Sudhir Kumar Singh; Sushil Kumar Singh; Tryambak Deo Singh; Meenakshi Singh (Elsevier, 2022)
Indole-containing small molecules have been reported to have diverse pharmacological activities. The aromatic heterocyclic scaffold, which resembles various protein structures, has received attention from organic and medicinal chemists. Exploration of indole derivatives in drug discovery has rapidly yielded a vast array of biologically active compounds with broad therapeutic potential. Nature is the major source of indole scaffolds, but various classical and advanced synthesis methods for indoles have also been reported. One-pot synthesis is widely considered an efficient approach in synthetic organic chemistry and has been used to synthesize some indole compounds. The rapid emergence of drug-resistant tuberculosis is a major challenge to be addressed. Identifying novel targets and drug candidates for tuberculosis is therefore crucial. Researchers have extensively explored indole derivatives as potential anti-tubercular agents or drugs. Indole scaffolds containing the novel non-covalent (decaprenylphosphoryl-β-D-ribose2'-epimerase) DprE1 inhibitor 1,4-azaindole is currently in clinical trials to treat Mycobacterium tuberculosis. In addition, DG167 indazole sulfonamide with potent anti-tubercular activity is undergoing early-stage development in preclinical studies. Indole bearing cationic amphiphiles with high chemical diversity have been reported to depolarize and disrupt the mycobacterial membrane. Some indole-based compounds have potential inhibitory activities against distinct anti-tubercular targets, including the inhibition of cell wall synthesis, replication, transcription, and translation, as summarized in the graphical abstract. The success of computer-aided drug design in the fields of cancer and anti-viral drugs has accelerated in silico studies in antibacterial drug development. This review describes the sources of indole scaffolds, the potential for novel indole derivatives to serve as anti-tubercular agents, in silico findings, and proposed actions to facilitate the design of novel compounds with anti-tubercular activity.